Multiple Transcription Factor Profiling by Enzyme-Linked Immunoassay - Z. Shen; J. Peedikayil; G.K. Olson; P.D. Siebert; Y. Fang (BioTechniques)
Transcription factor-DNA interactions have been widely studied in the regulation of gene expression. We have established an enzyme-linked immunoassay platform to quantify specific transcription factor-DNA interactions. In our assay, dsDNA immobilized on a 96-well plate captures the transcription factor from the nuclear extract of mammalian cells. The DNA-bound transcription factor is detected and quantified by enzyme-linked immunoassay using a transcription factor-specific antibody. We have profiled multiple transcription factors involved in inflammation including NFκB p50, NFκB p65, c-Rel, c-Fos, CREB-1, and ATF-2. When compared with the traditional electrophoretic mobility shift assay, the enzyme- linked immunoassay shows a 10-fold higher sensitivity, eliminates the use of radioactivity, allows for a high-throughput format, and is faster.